Phase-based constitutive modeling and experimental study for dynamic mechanical behavior of martensitic stainless steel under high strain rate in a thermal cycle. (October 2016) - Nie, Zhenguo; Wang, Gang; Yu, Jianchao; Liu, Dehao; Rong, Yiming (Kevin)
Highlights: A phase-based constitutive model was proposed to predict the dynamic mechanical behavior of the martensite stainless steel in a complete heating and cooling cycle. The phase transformation must be considered under elevated temperature and high strain rate. The complete tests were conducted by using thermal compressive deformation via a Split Hopkinson pressure bar and Gleeble 3500, with a temperature range from 20 °C to 1000 °C, and a strain rate range from 0.001 s − 1 to 16, 000 s − 1 . Phase transformation kinetics was involved for the dual-phase regions, and a modified Johnson-Cook model was employed to determine the dynamic mechanical behavior of single phases. The stress forms a flow stress loop in a complete heating and cooling cycle, and the flow stress is not a single-valued function at a certain temperature and strain rate. It is a function of strain, strain rate, temperature and temperature history. Abstract: The material of turbine blades undergoes a complete thermal cycle in creep-feed grinding. The flow stress in the cycle has a significant effect on the residual stress, microtopography, and surface integrity. This study presents a phase-based constitutive model for describing the dynamic mechanical behavior of martensitic stainless steel in a complete thermal cycle. The complete tests were conducted by using thermal compressive deformation via Split Hopkinson Pressure Bar and Gleeble 3500, with temperature ranging from 20 °C to 1000 °C, and strain rate ranging from 0.001 s − 1 to 16, 000 s − 1 . Phase transformation kinetics was involved for the dual-phase region, and a modified Johnson–Cook model was employed to determine the dynamic mechanical behavior of single phase. The prediction of the phase-based model correlates well with the experimental data on stress–strain curves. The flow stress is demonstrated to form a loop in a complete thermal cycle, and the results indicated that the temperature history must be considered in the evolution of flow stress in terms of strain, strain rate, and temperature. Graphical abstract: